The Influence of Price Perceptions and Product Quality on Netflix Customer Satisfaction in Surabaya City - Dimas Khadafi; Rizky Dermawan (Jurnal Ekonomi dan Bisnis Digital, 2023)
Entertainment in the present has become an unavoidable need for society. One of the things that must be considered in creating an entertainment platform is, of course, paying attention to several factors so that it can run smoothly. This research itself analyzes the Netflix platform, which is a well-known Video-on-demand platform and one of the market leaders in the streaming platform industry. This study aims to examine the effect of Perceived Price and Product Quality on Netflix Consumer Satisfaction in the City of Surabaya. In collecting the data, the researcher distributed questionnaires via Google Form with 100 respondents, namely consumers who had bought Viva Cosmetics Lipstick in Blitar City. A purposeful sampling method was used in this study. The analysis was carried out using Partial Least squares (PLS). The results of this study showed that Perceived Price and Product Quality had a significant positive effect on Netflix Consumer Satisfaction in the City of Surabaya.